KRISIS UTANG SRI LANKA DALAM KERJA SAMA PEMBANGUNAN PROYEK PELABUHAN HAMBANTOTA DENGAN TIONGKOK - Azalia Hasanah, Rona; Afriani Sinulingga, Anita; Anggraini Austin, Diah (Hubungan Internasional Universitas Andalas, 2022)
This research aims to analyze the cause of Sri Lanka’s debt crisis in Hambantota Port Development Project with Tiongkok. Hambantota Port was built in order to turn the wheels of the economy that had been collapsed after 25 years of civil war. Besides, this port is located in strategic position in international shipping lines and this urged China to cooperate with Sri Lanka by funding most of the port development cost. However, the project that was supposed to enhance Sri Lanka’s economy, leads Sri Lanka into debt crisis. This research uses Theodore H Cohn’s concept of debt crisis in nation level. Data collection techniques and analysis were carried out using qualitative methods and explanative approaches. This study found that Sri Lanks’s debt crisis occurs because of irresponsible behavior of the both party that participated in this cooperation. China as the creditor aggresively lends Sri Lanka without respectively looking at Sri Lanka’s credit liability. On the other hand, Sri Lanka as the debtor tends to avoid the conditions that they thought as burdensome for them and the government was not able to handle the prolonged budget deficit, not able to make a good policy in facing debt situation, lack of transparency and high level of corruption.